2022
DOI: 10.3389/fenvs.2022.812648
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Machine Learning Algorithms in Predicting the Productivity of Conservation Agriculture at a Global Scale

Abstract: Assessing the productive performance of conservation agriculture (CA) has become a major issue due to growing concerns about global food security and sustainability. Numerous experiments have been conducted to assess the performance of CA under various local conditions, and meta-analysis has become a standard approach in agricultural sector for analysing and summarizing the experimental data. Meta-analysis provides valuable synthetic information based on mean effect size estimation. However, summarizing large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Visualization tools are more and more often applied to identify the main factors of crop yield variations using RF or similar ML algorithms (e.g. in [37,53,54]). Here, we used importance ranking and partial dependence plots to identify the most influential predictors and found that precipitations and temperatures were the most important (Supplementary Figures 3 and 15), which is consistent with previous studies [55] and with our knowledge on soybean physiology [56].…”
Section: Discussionmentioning
confidence: 99%
“…Visualization tools are more and more often applied to identify the main factors of crop yield variations using RF or similar ML algorithms (e.g. in [37,53,54]). Here, we used importance ranking and partial dependence plots to identify the most influential predictors and found that precipitations and temperatures were the most important (Supplementary Figures 3 and 15), which is consistent with previous studies [55] and with our knowledge on soybean physiology [56].…”
Section: Discussionmentioning
confidence: 99%